Research Trends on Gender Bias in the Workplace: A Bibliometric Analysis - Verica Sofie Putibungsu; Leni Anjani; Puspita Sari; Tri Na’imah (Westscience Press, 2026)
This study examines research trends related to gender bias in the workplace through a bibliometric analysis. Data were retrieved from the Scopus database, yielding 821 publications published between 2022 and 2026. The analysis employed VOSviewer and Bibliometrix to explore publication patterns, thematic structures, and the evolution of research in this field. The results reveal a substantial growth in the number of publications during the study period, indicating increasing scholarly interest in workplace gender bias. Keyword co-occurrence analysis revealed that research themes have expanded from gender inequality and discrimination to broader topics such as intersectionality, women’s empowerment, leadership, workplace diversity, and job satisfaction. The United States and the United Kingdom were identified as the most influential contributors in terms of publication output and research collaboration. Overall, the study highlights the evolution of research on gender bias in the workplace and provides insights into future research directions as well as the development of more inclusive organizational policies.